Knowledge Encyclopedia - Kingsley;Dorling (London DK, 2013)
Offers a visual approach to learning about the wonders of our world. This title uses the CGI technology to help you explore what you wanted to know more about, covering space, Earth, nature, the human body, history and culture, and science and technology in incredible detail.